PENGUNAAN MICROSOFT EXCEL DALAM PERHITUNGAN INDEKS KEPUASAN MASYARAKAT (Study Kasus Pada Unit Pelayanan Sim Satlantas Kota Bekasi) - Feri Prasetyo H (Universitas Bina Sarana Informatika, 2014)
Microsoft Excel is a spreadsheet application that can be used in business applications Community satisfaction index, is a data and information about the level of community satisfaction with the results obtained from the public opinion in obtaining the services of officials of public service providers by comparing the expectations and needs. 14 elements of the